Recent Advances in Chemoenzymatic Peptide Syntheses - Yazawa, Kenjiro (Molecules, 2014)
Chemoenzymatic peptide synthesis is the hydrolase-catalyzed stereoselective formation of peptide bonds. It is a clean and mild procedure, unlike conventional chemical synthesis, which involves complicated and laborious protection-deprotection procedures and harsh reaction conditions. The chemoenzymatic approach has been utilized for several decades because determining the optimal conditions for conventional synthesis is often time-consuming. The synthesis of poly- and oligopeptides comprising various amino acids longer than a dipeptide continues to pose a challenge owing to the lack of knowledge about enzymatic mechanisms and owing to difficulty in optimizing the pH, temperature, and other reaction conditions. These drawbacks limit the applications of the chemoenzymatic approach. Recently, a variety of enzymes and substrates produced using recombinant techniques, substrate mimetics, and optimal reaction conditions (e.g., frozen aqueous media and ionic liquids) have broadened the scope of chemoenzymatic peptide syntheses. In this review, we highlight the recent advances in the chemoenzymatic syntheses of various peptides and their use in developing new materials and biomedical applications.